Impact of seasonings on sensory attributes of beef across three cuts of steak and two USDA grades - Whetstone, Sara (Kansas State University, 2012)
Three cuts of steak (strip, chuck-eye and top blade) of two United States Department of Agriculture grades (choice and select) underwent seasoning and tenderization treatments to study whether flavor and texture quality could be enhanced within cut and grade of steak. Treatments included: 1) seasoning alone, 2) a combination of seasoning + bromelain (enzymatic tenderizer), or 3) control (no seasoning and/or bromelain). The seasoning included: kosher salt, black pepper, onion powder, garlic powder, cumin, and ground oregano. All of the steaks were cooked to an internal temperature of 71° C (medium doneness). Six trained descriptive panelists evaluated the samples. The results of this study indicate that it may be possible to improve eating quality of choice and select chuck-eye and choice top blade to be more similar to strip steaks of the same USDA grade. Both treatments increased flavor and texture attributes in these samples that have been shown to have an impact on liking scores. Choice chuck-eye samples had decreased bloody/serumy and metallic scores and increased umami and initial flavor impact with both treatments. Both treatments increased brown/roasted flavor in select chuck-eyes. Tenderness, fat-like and umami were increased with the seasoning + bromelain treatment in select chuck-eyes. Choice top blade steaks with seasoning alone had increased umami flavor. Both treatments impacted attributes (fat-like, umami and sour) of the select strip steak that differed from choice strip steaks. The next step to this research is to investigate whether consumer liking scores are consistent with conclusions made from descriptive analysis results. Overall, these treatments could be a valuable tool for beef retailers.
Keywords: Sensory; Descriptive analysis; Beef; Seasoning; Animal Sciences (0475); Food Science (0359)